2007
DOI: 10.1021/jo062114k
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Synthesis of Substituted (Diphenylphosphinoylmethyl)benzenes

Abstract: An efficient protocol for the synthesis of structurally diverse (diphenylphosphinoylmethyl)benzenes is described. The reaction employs readily available carboxylic acids, chlorodiphenylphosphine, and water as the reagents. A 97% reduction in the reaction times and substantially higher yields of products result, up to a 60% increase, if the reactions are performed under microwave irradiation. The first examples of transition-metal-catalyzed reactions applied to 4-bromo-1,3-bis(diphenylphosphinoylmethyl)benzene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Conventionally, heating arenecarboxylic acids, Ph 2 PCl (3 equiv), and water (2 equiv) at a high reaction temperature (180 °C) for a long time (100 h) produced the corresponding benzyl phosphoryl compounds. 19 Microwave irradiation improved the reaction to some extent; 20 however, the method still did not find application in organic synthesis due to the harsh reaction conditions. In 2020, Yamaguchi and co-workers described the deoxygenative phosphorylation of aromatic esters by P(O)-H compounds forming benzylic phosphoryl compounds through palladium catalysis (Scheme 5).…”
Section: Scheme 3 Cu-catalyzed and Aldehyde-induced Tandem Decarboxylmentioning
confidence: 99%
“…Conventionally, heating arenecarboxylic acids, Ph 2 PCl (3 equiv), and water (2 equiv) at a high reaction temperature (180 °C) for a long time (100 h) produced the corresponding benzyl phosphoryl compounds. 19 Microwave irradiation improved the reaction to some extent; 20 however, the method still did not find application in organic synthesis due to the harsh reaction conditions. In 2020, Yamaguchi and co-workers described the deoxygenative phosphorylation of aromatic esters by P(O)-H compounds forming benzylic phosphoryl compounds through palladium catalysis (Scheme 5).…”
Section: Scheme 3 Cu-catalyzed and Aldehyde-induced Tandem Decarboxylmentioning
confidence: 99%
“…With the same Ph 2 PCl, Ishibashi showed that the reductive phosphorylation of trifluoroacetic acid (TFA) was successful and the reaction time could be dramatically shortened when the mixture was prestirred (80 h vs. 2.5 h) (Scheme 18 A, left) [137] . Capitalizing on microwave irradiation, Bew and his group slightly extended the scope to aromatic carboxylic acids, which gave several synthetically useful (diphenylphosphinoylmethyl)benzenes in moderate yields (Scheme 18 A, right) [138] …”
Section: Deoxygenative Functionalizations Of Carboxylic Acidsmentioning
confidence: 99%
“…[137] Capitalizing on microwave irradiation, Bew and his group slightly extended the scope to aromatic carboxylic acids, which gave several synthetically useful (diphenylphosphinoylmethyl)benzenes in moderate yields (Scheme 18 A, right). [138] In 2020, Yamaguchi disclosed ag eneral deoxygenative phosphorylation method by means of palladium catalysis (Scheme 18 B). [139] When the notoriously reactive Ph 2 PCl was replaced with disubstituted phosphine oxide and sodium formate (HCO 2 Na), abroad range of benzylated phosphorus compounds could be obtained from free acids (18.1 and 18.2) or premade phenyl esters (18.3 to 18.5).…”
Section: Noncatalytic Reductive Amination Of Carboxylic Acidsmentioning
confidence: 99%